2023
DOI: 10.1002/slct.202203862
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Theoretical Study of the Conformational Stability of Triazinone Fleximers: Quantitative Analysis for Intermolecular Interactions

Abstract: Synthesis and characterization of triazinone based propylene linked phthalimide and benzimidazole have been carried out for conformational analysis and the study of their quantitative intermolecular interactions. The conformational analyses have been calculated by X-ray crystallography in the solid state and theoretical calculations in the gaseous state. From the crystal structure and theoretical calculations we have found that all compounds are stable in the folded conformation. These stable conformations are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…This result emphasized the significance of intermolecular interactions on the DPP-IV inhibiting activity of peptides. Similarly, the conformation of triazinones was also observed to be folded specially and be stabilized by intermolecular interactions . Purushothaman et al also reported that the existence of intermolecular interaction was related to the biological activity of molecules .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This result emphasized the significance of intermolecular interactions on the DPP-IV inhibiting activity of peptides. Similarly, the conformation of triazinones was also observed to be folded specially and be stabilized by intermolecular interactions . Purushothaman et al also reported that the existence of intermolecular interaction was related to the biological activity of molecules .…”
Section: Resultsmentioning
confidence: 93%
“…Similarly, the conformation of triazinones was also observed to be folded specially and be stabilized by intermolecular interactions. 37 Purushothaman et al also reported that the existence of intermolecular interaction was related to the biological activity of molecules. 38 We also investigated the influence of different intramolecular interactions on their activities.…”
Section: Effect Of Intramolecular Interaction Of Xaa−pro-type Dpp-iv ...mentioning
confidence: 98%
“…Moreover, AIE-active fluorescent powder can be adsorbed on matrices (which are < 10 nm range, non-toxic, biocompatible and have excellent physicochemical properties) to image high quality fingerprints on different porous and non-porous surfaces. [33][34][35][36][37][38][39][40][41] In continuation of our interest towards synthesis of solidstate emitters based on naphthalimide and perylene diimide, [13][14][15][42][43][44] herein, we have synthesized compound 2 based on HBT scaffold. For convenience in use and application, 2 has been adsorbed on silica.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our interest towards synthesis of solid‐state emitters based on naphthalimide and perylene diimide, [13–15,42‐44] herein, we have synthesized compound 2 based on HBT scaffold. For convenience in use and application, 2 has been adsorbed on silica.…”
Section: Introductionmentioning
confidence: 99%